Geometric properties of generalized symmetric spaces. Issue 1 (30th January 2015) - Calviño-Louzao, Esteban; García-Río, Eduardo; Vázquez-Abal, María Elena; Vázquez-Lorenzo, Ramón
Abstract : It is shown that four-dimensional generalized symmetric spaces can be naturally equipped with some additional structures defined by means of their curvature operators. As an application, those structures are used to characterize generalized symmetric spaces.